Psihološki vidiki proceduralne bolečini ! pri otroku in uporaba kognitivno-vedenjskega pristopa - Bürger-Lazar, Martina (Psihološka obzorja (Ljubljana), 2020)
Medical procedures are often associated with a high degree of distress in children. Negative experience related to recurrent painful medical procedures in the childhood may have long-term negative psychological effects. Therefore, besides pharmacological interventions, different cognitive-behavioural techniques are very helpful in reducing child distress and pain perception. However, there is no standard method equally suitable for all children. The most appropriate intervention should be carefully chosen for each individual child, taking into consideration the characteristics of the medical procedure, knowledge of factors affecting pain perception and the child's personality. Scientific research in which the effect of various psychological approaches to preparing children for (painful) medical procedures was studied shows that cognitive-behavioural interventions are the most effective in reducing pain and distress in children, and should therefore be used in clinical practice.
Keywords: bolečina; children; cognitive behavior therapy; kognitivno vedenjska terapija; merjenje bolečine; otroci; pain; pain measurement; pain perception; zaznavanje bolečine